War and finance in the unified Argentina, 1864-1872. The Paraguay War and the mission of Norberto de la Riestra in London (Quinto Sol, 2016)
This study examines one aspect of the Argentinian financial issue linked to the Paraguay War: the mission that is entrusted to Norberto de la Riestra to obtain in London a loan of £2,500,000 to finance part of the costs of the conflict. This single event allows us to open a window into several closely related issues: external and internal Argentinian debt, ways of financing these debts and links with the ups and downs of the world economy at the beginning of the great international crisis of 1873/1876.
Keywords: Paraguay War; debts; state building; financial markets; international crisis